2014
DOI: 10.1093/eurheartj/ehu240
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcome in Sweden after out-of-hospital cardiac arrest and possible association with improvements in every link in the chain of survival

Abstract: From a long-term perspective, 30-day survival after OHCA in Sweden more than doubled. The increase in survival was most marked among patients found in a shockable rhythm and those hospitalized with ROSC. There were improvements in all four links in the chain of survival, which might explain the improved outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 37 publications
(28 reference statements)
9
103
2
4
Order By: Relevance
“…In our study, the arrival time was 9 min. This result is comparable to international data [7,9,14,[18][19][20]29].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the arrival time was 9 min. This result is comparable to international data [7,9,14,[18][19][20]29].…”
Section: Resultssupporting
confidence: 90%
“…Comparing the data with literature, a significant discrepancy can be noted, especially with the countries of Western Europe where the numbers are two or three times lower [2]. On the basis of international data, the standard OHCA incidence rate ranges from 34/100,000 (Denmark) [5], through 51/100,000 (Finland) [6], 52/100,000 (Sweden) [7], and 88/100,000 (Ireland), [8] to 206/100,000 (Austria) [9]. These detectable differences can be explained by two major facts: on the one hand, it is related to the characteristics of patients and circumstances of the incident, and on the other hand, to the system of reporting results.…”
Section: Resultsmentioning
confidence: 76%
“…These reforms likely led to a more rapidly initiated chain of survival that would have contributed to our documented increase in the percentage of defibrillated patients (Table 2) and earlier CPR. This may have contributed to our overall improved bystander‐witnessed survival, survival to hospital admission, and overall survival, as documented in other studies 17, 18, 19…”
Section: Discussionsupporting
confidence: 67%
“…For comparison, in Sweden, the average response time of the rescue system for patients who survived SCA was 11 min and 15 min in cases of death. The authors of this study also indicated that a higher survival rate was observed in areas where more ambulances are based, and not on the density of population [17]. In one research project conducted in Poland the authors defined that ambulance arrival time was 9 min for patients with ROSC and 11 min for deceased.…”
Section: Discussionmentioning
confidence: 79%